New voices of Muslim North-African migrants in Europe - Ricci, Cristián (BRILL, 2020)
New Voices of Muslim North-African Migrants in Europe captures the experience in writing of a fast growing number of individuals belonging to migrant communities in Europe. The book follows attempts to transform postcolonial literary studies into a comparative, translingual, and supranational project. Cristián H. Ricci frames Moroccan literature written in European languages within the ampler context of borderland studies. The author addresses the realm of a literature that has been practically absent from the field of postcolonial literary studies (i.e. Neerlandophone or Gay Muslim literature). The book also converses with other minor literatures and theories from Sub-Saharan Africa, as well as Asians and Latino/as in the Americas that combine histories of colonization, labor migration, and enforced exile.